DOZ047.99: A unique case of 'esophageal trachea' requiring a multistep sequential surgical reconstruction. (24th June 2019) - Tambucci, R; Wautelet, O; François, G; Haenecour, A; Goubau, C; Scheers, I; de Toeuf, C; Schmitz, S; Menten, R; Pirotte, T; D'hondt, B; Reding, R; et al.
Abstract: Introduction: Communicating bronchopulmonary foregut malformations (CBPFMs) have been defined by Srikanth et al. in 1992 as a fistula between a portion of respiratory tissue and esophagus/stomach. Four types of CBPFMs have been described, none of those contemplating a complete communication between the distal trachea and esophagus. Case Report: This study reports a case of a full-term neonate presenting with a VACTERL association and a tracheoesophageal malformation characterized by the presence of a long common duct including both the middle esophagus and distal trachea, which consists in esophageal tissue, without any cartilaginous rings 3–4 cm above the carina. A few days after birth, the esophagus and trachea have been surgically separated, keeping the common duct on the tracheal side and creating a residual long-gap esophageal atresia (LGEA). The resulting severe tracheomalacia has been simultaneously treated by posterior splinting using an autologous pericardium patch, as well as by anterior aortopexy. A terminal esophagostomy and a gastrostomy have been created to postpone esophageal reconstruction. Since the age of 18 months, delayed repair of LGEA has been performed by using a multistep strategy consisting of a combination of Kimura extrathoracic esophageal elongations and distal stump Foker external traction. Since no cartilaginous rings were present, refractory tracheomalacia has been further treated by a tracheoplasty through a combined median sternotomy and tracheoscopy approach at the age of 3 years by using a semitubular rigid Gore-Tex® prosthesis for an anterior external stenting. Today, 9 months after last surgery, complete weaning from respiratory support has been stably achieved, as well as full oral feeding. Conclusions: This is the first description of an 'esophageal trachea', which may be considered as a new anatomic variant of CBPFMs. Multidisciplinary medical and surgical expertise was needed to manage this particular case, in order to properly plan multiple sequential surgical approaches. Native esophageal reconstruction should always be considered, even because colonic or gastric transposition might further affect severe tracheomalacia, resulting in more challenging treatment.